Regional Cerebral Blood Flow Using Quantitative MR Angiography - Zhao, M.; Amin-Hanjani, S.; Ruland, S.; Curcio, A.P.; Ostergren, L.; Charbel, F.T. (American Journal of Neuroradiology, 2007)
BACKGROUND AND PURPOSE: We sought to derive regional cerebral blood flow using vessel flows from quantitative MR angiography (qMRA).MATERIALS AND METHODS: Flow rates in the 15 major cerebral arteries were measured on retrospectively gated fast 2D phase-contrast MR angiography obtained in 83 healthy adult volunteers (age range, 24–74 years; mean, 42 years). The arterial network of the brain was partitioned into 12 different regions, in which flows were calculated from the measured flows of the 15 cerebral arteries.RESULTS: The mean flows of the 15 arteries and the 12 regions were calculated. The mean total cranial flow and the mean total cerebral blood flow were 949 extpm 158 mL/min and 695 extpm 113 mL/min, respectively. The mean regional flows for the anterior and posterior circulation were 483 extpm 87 mL/min and 212 extpm 34 mL/min, respectively. The relative contributions of the flows in the 11 regions to their parent regions were obtained. The mean flows in the individual arteries and the regions with age were also calculated. The mean flows for the female group were significantly lower than those for the male group (P < .001) for the 2 common carotids and the cranial circulation and left/right extracranial circulation. However, the intracranial circulation was not different between sexes.CONCLUSIONS: The 12 regions in the cerebral circulation were identified and formed into a partition tree, and the mean regional flow for each region was determined using vessel flows from qMRA.